PENGEMBANGAN USAHA SAPI POTONG KELOMPOK TANI TERNAK HIDAYAH KAMPUNG LABAN KENAGARIAN SALIDO KABUPATEN PESISIR SELATAN - Hanafi Herman; Fuad Madarisa; Syahrial Syahrial (Jurnal Bisnis Tani, 2018)
This study aims to determine the condition of planning owned by Farmers Group of Livestock Hidayah and formulated Development Plan Beef Cattle farmer group. This research was conducted in Pesisir Selatan Regency with 13 group members, 1 officer of Artificial Insemination and 1 PPL Sub Districk IV Jurai. The data source consists of: (a) Primary data using qustionnaires and Focus Group Discusiion (FGD) and (b) secondary data obtained fromAnimal Husbandry and Animal Health Service and Central Bureau of Statistics of Pesisir Selatan Regency. Both types of data were analyzed descriptively qualitative. The results of the study show that the Hidayah Farmers Group currently has 13 members. The election of group officials is done nominating candidates and elected by the members. Age group members are at the age of 36-45 years, which indicates that group members are still in productive age. The level of education of most group members is at the high school level.Furthermore, the planning of the group already has a plan even though it has not been written.Business Development Plan of Beef Cattle Group of Hidayah Livestock Farm consistsof 23 activities. Plan include, provision of seeds, feed cages, diseases, markets, group administration, member comptencies, human resource development, facilities and infrastructure, communication networks and financing sources.